Factors influencing trust among colleagues in hospital settings: a systematic review - Andreea Isabela Varga; Ivan Spehar; Frode Veggeland; Helge Skirbekk (BMC Health Services Research)
Abstract Background Many studies show positive results of collegial trust in the workplace, e.g. performance, innovation and collaboration. However, no systematic review on collegial trust in hospital settings exists. This study aimed to provide the missing overview of factors that positively and negatively influence this trust relationship between healthcare providers. Methods Ten information sources (Web of Science, Embase, MEDLINE, APA PsycInfo, CINAHL, Scopus, EconLit, Taylor & Francis Online, SAGE Journals and Springer Link) were searched from database inception up until October 21st, 2022. Empirical studies included were written in English, undertaken in a hospital or similar setting, and addressed collegial trust relationships between healthcare professionals, without date restrictions. Studies were excluded if they only explored trust between healthcare professionals on different hierarchical levels. Theoretical studies, systematic reviews, conceptually unclear papers and anecdotal case studies were also excluded. Records were independently screened for eligibility by at least two researchers. A narrative synthesis technique was adopted to explore and discuss the influencing factors of trust between colleagues identified across both quantitative and qualitative studies. This method was chosen given the inclusion of studies with different research designs and the unsuitability of the data for a meta-analysis or meta-ethnography. Risk of bias was assessed independently by at least two researchers using four critical appraisal tools. Results Eight thousand two hundred sixty-eight studies were screened and 11 studies were included. Seven were qualitative and four were quantitative. Themes identified were professional competence, elements of communication, such as tacit knowledge sharing, and ethical conduct, such as honesty, confidentiality and accountability. Moreover, trust among colleagues was seen to thrive in work environments characterised by psychological safety. The results of the quality assessment show that most studies were of an acceptable quality, with some associated risk of bias. One of the limitations was represented by the lack of a definition for trust in some studies, and some inconsistency for those studies that did define trust. Conclusions Professionalism, communication and ethics were seen as the most important factors enhancing trust. However, these concepts were defined differently in the studies. Trial registration PROSPERO; CRD42023433021.